Improved adhesive resins
By using epoxy crosslinking agents and polyamines in the binder resin, combining lignin with carbohydrates, and accelerating the reaction with ammonia and organic alkali, the problem of dry and wet strength balance of phenol-formaldehyde type binder substitutes is solved. , improves the performance and reaction rate of insulating materials.
Patent Information
- Application Number
- CN202380041200.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, alternatives to phenol-formaldehyde type adhesives are difficult to balance the properties of dry strength and wet strength in the manufacturing of fiberglass insulating materials, particle boards and auditory sound insulation materials, and the reaction rate is low. , affects the performance of the product.
Using epoxy-based crosslinking agent and polyamine reaction products, combining lignin with carbohydrate reactants, to improve reactivity and performance by adding aqueous solution of ammonia and/or organic base to the binder resin to improve reactivity and performance. adhesive resin.
It significantly improves the balance of wet and dry strength of the bonding resin, shortens the curing time, is suitable for the manufacturing of insulating materials, and reduces the risk of degradation of fibers.
Smart Images

Figure BDA0005139341000000121 
Figure BDA0005139341000000131 
Figure BDA0005139341000000132
Abstract
Description
Technical Field
[0001] The present invention relates to a binding resin which can be used, for example, in the manufacture of insulation materials such as mineral wool insulation materials or glass wool insulation materials. The present invention also relates to a process for preparing the binding resin and to its use. Background Art
[0002] Adhesive resins can be used to manufacture articles because they can consolidate non-assembled or loosely assembled materials. For example, adhesive resins enable two or more surfaces to be united. In particular, adhesive resins can be used to produce products comprising consolidated fibers. Thermosetting adhesive resins can be characterized in that they are converted into insoluble and infusible materials by either heating or catalysis. Examples of thermosetting adhesive resins include multiple phenol-formaldehyde, urea-formaldehyde, melamine-formaldehyde and other condensation-polymerization materials like polyurethane resins. Adhesive resins containing phenol-formaldehyde, resorcinol-formaldehyde, phenol / formaldehyde / urea, phenol / melamine / aldehyde, etc. are used for the bonding of fibers, fabrics, plastics, rubber and many other materials.
[0003] The mineral wool and fiberboard industries have historically used phenol-formaldehyde binder resins to bind the fibers. Phenol-formaldehyde type binder resins provide suitable properties for the final product; however, environmental considerations have stimulated the development of alternative binders. One such alternative binder resin is a carbohydrate-based binder derived from reacting a carbohydrate with a polyprotic acid, for example according to US2007 / 0027283 and WO2009 / 019235. Another alternative binder resin is the esterification product of a polycarboxylic acid reacted with a polyol, for example according to US2005 / 0202224. Since these binders do not utilize formaldehyde as a reagent, they have been collectively referred to as formaldehyde-free binders.
[0004] One area of development is to find substitutes for phenol-formaldehyde type adhesives across the entire range of products (e.g., fiberglass insulation, particleboard, office panels, and acoustic sound insulation) that use phenol-formaldehyde type adhesives. In particular, previously developed formaldehyde-free adhesive resins may not have all the desired properties for all products. For example, adhesives based on acrylic acid and poly(vinyl alcohol) have shown promising performance characteristics. However, these are relatively more expensive than phenol-formaldehyde adhesives, are substantially derived from petroleum-based resources, and have a tendency to exhibit lower reaction rates (either requiring longer curing times or requiring increased curing temperatures) compared to phenol-formaldehyde-based adhesive resins. Carbohydrate-based adhesive resins are made from relatively inexpensive precursors and are primarily derived from renewable resources; however, these adhesive resins may also require reaction conditions for curing that are substantially different from those under which traditional phenol-formaldehyde adhesive systems are cured. Therefore, it is not yet easily achievable to replace phenol-formaldehyde type adhesives with existing substitutes.
[0005] EP2566904 relates to adhesive formulations comprising the reaction product of a carbohydrate reactant and a polyamine and materials made using the same.
[0006] Lignin, an aromatic polymer, is the main component of wood, and is the most abundant carbon source on Earth after cellulose. In recent years, with the development and commercialization of technologies to extract highly purified, solid and particularized forms of lignin from pulping processes, it has attracted great attention as a possible renewable alternative to the main aromatic chemical precursors currently derived from the petrochemical industry.
[0007] Lignin, a polyaromatic network structure, has been extensively studied as a suitable substitute for phenol during the production of phenol-formaldehyde adhesives. These are used during the manufacture of laminates and structural wood products such as plywood, oriented strand board and fiberboard. During the synthesis of such adhesives, phenol (which can be partially replaced by lignin) reacts with formaldehyde in the presence of either alkaline or acidic catalysts to form highly cross-linked aromatic resins, known as novolacs (when utilizing acidic catalysts) or resols (when utilizing alkaline catalysts). Currently, only a limited amount of phenol can be replaced by lignin due to the lower reactivity of lignin.
[0008] A particular problem in preparing insulation products is obtaining a suitable balance between dry and wet strength properties, which depends largely on the binding resin used. If the insulation product is intended for use in applications where it is exposed to moisture or water, such as for outdoor use, a binding resin must be used which provides sufficient wet strength. Summary of the invention
[0009] It has now surprisingly been found that a binding resin suitable for use, for example, in the production of insulating materials can be readily prepared wherein the use of formaldehyde can be avoided. It has also been found that the binding resin provides improved wet strength properties and an improved balance between dry and wet strength properties, making it particularly useful in the manufacture of insulating materials. Further, it has been found that the strength properties can be improved by including an epoxy-based crosslinking agent in the binding resin.
[0010] Further, it has been found that when lignin is provided in the form of an aqueous solution containing ammonia and / or an organic base, the phenolic hydroxyl groups in the lignin structure are deprotonated and are free to react with other components of the binder resin. This improves the reactivity and performance of the binder. Therefore, when manufacturing, for example, mineral wool insulation or glass wool insulation, providing lignin in the form of an aqueous solution containing ammonia and / or an organic base significantly accelerates the reaction rate and thus promotes the curing of the binder resin.
[0011] Furthermore, by providing the lignin in the form of an aqueous solution comprising ammonia and / or an organic base, the risk of degrading eg glass wool and mineral wool fibers is minimized.
[0012] The present invention thus relates to a binding resin comprising the reaction product of a carbohydrate reactant, lignin, an epoxy-based crosslinker and a polyamine, wherein the carbohydrate reactant is selected from a monosaccharide, a disaccharide or an oligosaccharide, and wherein the polyamine is a primary polyamine selected from a diamine, a triamine, a tetraamine and a pentamine, and wherein the polyamine is H2N-Q-NH2, wherein Q is C1-C 10 Alkyl, cycloalkyl, C1-C 10 heteroalkyl or cycloheteroalkyl, each of which is optionally substituted; and wherein the lignin is provided as a solution, and wherein the weight ratio of the carbohydrate and the polyamine is in the range of from 1:100 to 100:1, and wherein the weight ratio of the lignin and the carbohydrate is between 1:100 and 100:1, calculated on a dry lignin and dry carbohydrate basis, and wherein the amount of lignin in the binding resin is in the range of from 5 wt % to 30 wt %, calculated on a dry lignin and dry binding resin basis.
[0013] The invention also relates to a fibrous insulation product comprising a binding resin according to the invention. DETAILED DESCRIPTION
[0014] Throughout this specification, the expression "lignin" is intended to encompass any kind of lignin, such as lignin derived from hardwood, softwood or annular plants. Preferably, the lignin is an alkaline lignin generated in, for example, a Kraft process. Preferably, the lignin has been purified or separated before being used in the process according to the present invention. Lignin can be separated from black liquor and optionally further purified before being used in the process according to the present invention. Purification typically makes the purity of lignin at least 90%, preferably at least 95%. Thus, the lignin used according to the method of the present invention preferably contains less than 10%, preferably less than 5% impurities. Lignin can then be separated from black liquor using a process disclosed in WO2006031175. Lignin can then be separated from black liquor using a process called LignoBoost process. Lignin can be provided in the form of particles, such as particles with an average particle size from 50 microns to 500 microns. Lignin can also be provided in the form of agglomerates, the agglomerates having an average diameter from 0.01 to 10 mm, such as from 0.1 to 5 mm.
[0015] The reactivity of lignin can be increased by modifying the lignin via glyoxylation, etherification, esterification, amination or any other method that increases the hydroxyl content or carboxyl content or amine content or thiol content of the lignin. Preferably, the lignin used according to the present invention is not chemically modified after it is extracted and separated from wood. More specifically, the lignin is preferably not subjected to oxidation after it has been separated from the kraft process.
[0016] The aqueous solution of lignin containing ammonia and / or an organic base can be prepared by methods known in the art, for example, by mixing lignin and ammonia and / or an organic base with water. The pH of the aqueous solution of lignin containing ammonia and / or an organic base is preferably in the range of from 8 to 14, more preferably in the range of from 9 to 11 or 10 to 11. Examples of organic bases include amines, such as primary amines, secondary amines and tertiary amines and mixtures thereof. Preferably, the organic base is selected from methylamine, ethylamine, propylamine, butylamine, ethylenediamine, methanolamine, ethanolamine, aniline, cyclohexylamine, benzylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dimethanolamine, diethanolamine, diphenylamine, benzylamine, phenylethylamine, hexamethylenediamine, polyetheramine, dicyclohexylamine, piperazine, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-phenylimidazole, 2-methylimidazoline, 2-phenylimidazoline, trimethylamine, triethylamine, dimethylhexylamine, N-methylpiperazine, dimethylbenzylamine, aminomethylpropanol, tris(dimethylaminomethyl)phenol and dimethylaniline and mixtures thereof. The total amount of ammonia and / or organic base in the aqueous solution is preferably in the range of 0.1% to 20% by weight, preferably 0.1% to 10% by weight of the total weight of the aqueous solution containing water, lignin and ammonia and / or organic base. The amount of lignin in the aqueous solution containing ammonia and / or organic base is preferably from 1% to 60% by weight of the solution, such as from 10% to 30% by weight of the solution. The aqueous solution containing ammonia and / or organic base lignin contains less than 1% by weight alkali and less than 1% by weight inorganic base. More preferably, the aqueous solution containing ammonia and / or organic base lignin does not contain alkali and does not contain inorganic base.
[0017] The amount of lignin in the binding resin is preferably from 5% by weight to 50% by weight, calculated based on the dry weight of lignin and the total weight of the binding resin.
[0018] As used herein, polyamines are organic compounds with two or more amine groups. As used herein, primary polyamines are organic compounds with two or more primary amine groups (-NH2). Within the scope of the term primary polyamines are those compounds that can be in situ modified or isomerized to generate compounds with two or more primary amine groups (-NH2). Polyamines are primary polyamines.
[0019] The polyamine used in the adhesive resin according to the present invention may be a molecule having the formula H2N-Q-NH2, wherein Q is an alkyl, cycloalkyl, heteroalkyl or cycloheteroalkyl group, each of which may be optionally substituted. 24In one embodiment, Q is an alkyl group selected from C2-C8 alkyl groups. In one embodiment, Q is an alkyl group selected from C3-C7 alkyl groups. In one embodiment, Q is a C6 alkyl group. In one embodiment, Q is selected from cyclohexyl, cyclopentyl or cyclobutyl. In one embodiment, Q is benzyl.
[0020] As used herein, the term "alkyl" includes a chain of carbon atoms, which is optionally branched. Alkyl groups have a finite length and include C1-C 24 、C1-C 12 , C1-C8, C1-C6 or C1-C4. Shorter alkyl groups may add less hydrophilicity to the compound and accordingly will have different reactivity to carbohydrate reactants and lignin and solubility in the binder solution.
[0021] As used herein, the term "cycloalkyl" includes a chain of carbon atoms, which is optionally branched, wherein at least a portion of the chain is cyclic. Cycloalkylalkyl is a subset of cycloalkyl. Cycloalkyl may be polycyclic. Examples of cycloalkyl include, but are not limited to, cyclopropyl, cyclopentyl, cyclohexyl, 2-methylcyclopropyl, cyclopentyleth-2-yl, adamantyl, and the like. The chains forming cycloalkyls have a limited length, including C3-C 24 、C3-C 12 , C3-C8, C3-C6 or C5-C6. Shorter alkyl chains forming the cycloalkyl group may add less lipophilicity to the compound and will behave differently accordingly.
[0022] As used herein, the term "heteroalkyl" includes a chain of atoms including carbon and at least one heteroatom, and is optionally branched. Exemplary heteroatoms include nitrogen, oxygen and sulfur. Exemplary heteroatoms also include phosphorus and selenium. In one embodiment, heteroalkyl is a polyether. As used herein, the term "cycloheteroalkyl" including heterocyclic radicals and heterocycles includes a chain of atoms including carbon and at least one heteroatom, such as heteroalkyl, and is optionally branched, wherein at least a portion of the chain is cyclic. Exemplary heteroatoms include nitrogen, oxygen and sulfur. Exemplary heteroatoms also include phosphorus and selenium. Exemplary cycloheteroalkyl includes but is not limited to tetrahydrofuranyl, pyrrolidinyl, tetrahydropyranyl, piperidinyl, morpholinyl, piperazinyl, homopiperazinyl, etc.
[0023] As used herein, the term "optionally substituted" includes replacing hydrogen atoms with other functional groups on the optionally substituted group. Such other functional groups illustratively include, but are not limited to, amino, hydroxyl, halogen, thiol, alkyl, halogen alkyl, heteroalkyl, aryl, aralkyl, aryl heteroalkyl, nitro, sulfonic acid and derivatives thereof, carboxylic acid and derivatives thereof, etc. Exemplarily, any amino, hydroxyl, thiol, alkyl, halogen alkyl, heteroalkyl, aryl, aralkyl, aryl heteroalkyl and / or sulfonic acid is optionally substituted.
[0024] In one embodiment of the present invention, the polyamine is selected from diamines, triamines, tetramines and pentamines. In one embodiment, the polyamine is a diamine selected from hexamethylenediamine, 1,6-diaminohexane, 1,5-diamino-2-methylpentane and 3-(aminomethyl)-3,5,5-trimethylcyclohexane-1-amine. In one embodiment, the diamine is 1,6-diaminohexane. In one embodiment, the polyamine is a triamine selected from diethylenetriamine, 1-piperazineethaneamine and bis(hexamethylene)triamine. In one embodiment, the polyamine is a tetraamine such as triethylenetetramine. In one embodiment, the polyamine is a pentamine such as tetraethylenepentamine. In one embodiment, the primary polyamine is a polyether-polyamine. In one embodiment, the polyether-polyamine is a diamine or a triamine.
[0025] The carbohydrate reactant is a monosaccharide, a disaccharide or an oligosaccharide. In one embodiment, the carbohydrate is a monosaccharide in its aldose or ketose form. In one embodiment, the carbohydrate may be a reducing sugar. In one embodiment, the carbohydrate reactant is selected from glucose, xylose, fructose, dihydroxyacetone and mixtures thereof. In one embodiment, the carbohydrate reactant is a disaccharide such as sucrose, lactose or maltose. In one embodiment, the carbohydrate reactant is an oligosaccharide such as chitosan.
[0026] The weight ratio of carbohydrate to polyamine is in the range of from 1:100 to 100:1, calculated on a dry solids basis. Preferably, the weight ratio of carbohydrate reactant to polyamine is in the range of from 20:1 to 1:20, and more preferably in the range of from 10:1 to 1:10, most preferably in the range of from 1:3 to 10:1, such as in the range of from 1:2 to 5:1, or in the range of from 1:1.1 to 1.1:1, calculated on a dry solids basis.
[0027] The weight ratio of lignin to carbohydrates, calculated on a dry solids basis, is between 100:1 and 1:100, preferably in the range of 20:1 and 1:20, and more preferably in the range of from 10:1 to 1:10, most preferably in the range of from 1:1 to 10:1 such as from 1:1 to 5:1 or from 2:1 to 8:1 or from 2:1 to 5:1, or in the range of from 6:1 to 1:1, calculated on a dry solids basis.
[0028] The weight ratio of lignin to polyamine, calculated on a dry solids basis, is between 100:1 and 1:100, preferably in the range of 20:1 and 1:20, and more preferably in the range of from 10:1 to 1:10, most preferably in the range of from 2:1 to 10:1 such as from 1:1 to 5:1 or from 2:1 to 5:1, or in the range of from 6:1 to 1:1, calculated on a dry solids basis.
[0029] The epoxy-based crosslinking agent is preferably selected from glycerol diglycidyl ether, polyglycerol polyglycidyl ether, glycerol triglycidyl ether, sorbitol polyglycidyl ether, alkoxylated glycerol polyglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane diglycidyl ether, polyoxypropylene glycol diglycidyl ether, polyoxypropylene glycol triglycidyl ether, diglycidyl ether of cyclohexanedimethanol, resorcinol diglycidyl ether, isosorbide diglycidyl ether, pentaerythritol tetraglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether having 2 to 9 ethylene glycol units, propylene glycol diglycidyl ether having 1 to 5 propylene glycol units, carbohydrates. diglycidyl-, triglycidyl- or polyglycidyl-ethers of compounds, diglycidyl-, triglycidyl- or polyglycidyl-esters of carbohydrates, diglycidyl-ethers or diglycidyl esters of salicylic acid, vanillic acid or 4-hydroxybenzoic acid, epoxidized or glycidyl-substituted plant-based phenolic compounds or epoxidized plant-based oils, tris(4-hydroxyphenyl)methane triglycidyl ether, N,N-bis(2,3-epoxypropyl)aniline, p-(2,3-epoxypropyloxy-N,N-bis(2,3-epoxypropyl)aniline, diglycidyl ethers of bis-hydroxymethylfuran, and / or diglycidyl ethers of terminal diols having a linear carbon chain of 3 to 6 carbon atoms.
[0030] The weight ratio of epoxy-based crosslinker to lignin is preferably in the range from 1 :100 to 100:1 , more preferably in the range from 1 :100 to 10:1 , such as from 2:100 to 1 :1 or from 5:100 to 1 :1 , calculated on a dry solids basis.
[0031] The weight ratio of epoxy-based cross-linker to carbohydrate reactant is preferably in the range from 1 :100 to 100:1 , more preferably in the range from 1 :10 to 10:1 such as from 1 :5 to 5:1 , calculated on a dry solids basis.
[0032] The solid content of the adhesive resin before curing is preferably in the range from 10% to 70%, such as in the range from 15% to 50%.
[0033] The adhesive resin may also include additives such as urea, tannin, surfactant, dispersant and filler. The adhesive resin may also include plasticizer. In one embodiment, the adhesive resin does not include plasticizer. As used herein, the term "plasticizer" refers to such an agent, when added to lignin, by reducing the glass transition temperature (Tg) and improving its flow behavior, making lignin softer and more flexible to improve its plasticity. The example of plasticizer includes polyol, alkyl citrate (salt), organic carbonate (salt), phthalate (salt), adipate (salt), sebacate (salt), maleate (salt), benzoate (salt), trimellitate (salt) and organic phosphate (salt). Polyol includes for example polyethylene glycol, polypropylene glycol, glycerol, diglycerol, polyglycerol, butanediol, sorbitol and polyvinyl alcohol. Alkyl citrate includes for example triethyl citrate, tributyl citrate, acetylcitrate triethyl and trimethyl citrate.
[0034] Organic carbonates include, for example, ethylene carbonate, propylene carbonate, glycerol carbonate, and vinyl carbonate. Further examples of plasticizers include polyethylene glycol ethers, polyethers, hydrogenated sugars, triacetin, and solvents used as coalescing agents such as alcohol ethers. In one embodiment of the invention, the plasticizer is a polyol, such as a polyol selected from polyethylene glycol and polypropylene glycol. If the resin includes a plasticizer, the weight ratio between the plasticizer and the lignin is preferably from 0.1:10 to 10:1, calculated on the basis of the dry weight of each component. Preferably, the weight ratio between the plasticizer (if present) and the lignin is from 0.1:10 to 10:10, such as from 1:10 to 5:10, calculated on the basis of the dry weight of each component. The adhesive resin may also include a coupling agent. The coupling agent is, for example, a silane-based coupling agent. In one embodiment, the adhesive resin does not include a coupling agent.
[0035] Fillers and / or hardeners may also be added to the binding resin. Examples of such fillers and / or hardeners include limestone, cellulose, sodium carbonate and starch. In one embodiment, the binding resin does not contain fillers and / or hardeners.
[0036] Preferably, the binding resin according to the invention does not contain formaldehyde. Preferably, the binding resin does not contain phenol.
[0037] Preferably, the binder resin according to the present invention does not contain a basic catalyst. Further, preferably, no basic catalyst is used in the production of the binder resin according to the present invention.
[0038] Cellulosic materials used according to the present invention are, for example, mineral fibers (such as glass fibers, slag wool fibers and rock wool fibers), aramid fibers, ceramic fibers, metal fibers, carbon fibers, polyimide fibers, polyester fibers and rayon fibers. Such fibers are substantially unaffected by exposure to temperatures above about 120° C. In one embodiment, the insulating fibers are glass fibers. In one embodiment, the insulating fibers are rock wool fibers. In one embodiment, the mineral fibers are present in the insulation product according to the present invention in the range from about 70% by weight to about 99% by weight.
[0039] In one embodiment, the cellulosic material comprises cellulose fibers. For example, the cellulose fibers may be wood chips, sawdust, wood pulp, or milled wood. In one embodiment, the cellulose fibers may be other natural fibers such as jute, flax, hemp, and straw.
[0040] As used herein, the term adhesive solution is a solution of chemicals that can be substantially dehydrated to form an uncured adhesive resin. As used herein, the adhesive resin can be cured, uncured or partially cured. The composition of the uncured adhesive resin is called an uncured adhesive resin. The uncured adhesive resin is a substantially dehydrated mixture of chemicals that can be cured to form a cured adhesive resin. Substantially dehydrated means that the solvent (typically water or a mixture containing water) used to make the adhesive solution is evaporated to a sufficiently high degree that the viscosity of the remaining material (containing adhesive reactants and solvents) is sufficiently high to produce cohesion between loosely assembled substances; thus, the remaining material is an uncured adhesive resin. In one embodiment, the solvent is less than 65% of the total weight of the remaining material. In one embodiment, the substantially dehydrated adhesive resin has a moisture content of water between about 5% by weight and about 65% by weight of the total adhesive. In one embodiment, the solvent may be less than 50% of the total weight of the remaining material. In one embodiment, the solvent may be less than 35% of the total weight of the remaining material. In one embodiment, the substantially dehydrated binding resin has between about 10% and about 35% water by weight of the total binding resin. In one embodiment, the solvent may comprise less than about 20% of the total weight of the remaining materials.
[0041] As used herein, the term cured adhesive resin describes the polymer product of curing uncured adhesive resin. Cured adhesive resin can have characteristic brown to black color, and tends to absorb light in a wide range of wavelengths. Since the polymer of the cured adhesive resin is widely cross-linked, the cured adhesive resin is substantially insoluble. For example, the adhesive resin is substantially insoluble in water. As described herein, uncured adhesive resin provides sufficient bonding ability to consolidate the fibers; however, cured adhesive resin imparts firmness, long-lasting durability and physical properties conventionally associated with cross-linked polymers.
[0042] The binder resin reactants described herein are soluble in water, and when combined in water, a binder solution is obtained. In one embodiment, a surfactant is included in the aqueous solution to improve the solubility or dispersibility of one or more binder resin reactants or additives. For example, a surfactant can be added to the binder aqueous solution to enhance the dispersibility of the particulate additive. In one embodiment, a surfactant is used to produce an emulsion with a non-polar additive or binder reactant. In one embodiment, the binder solution includes about 0.01% by weight to about 5% by weight of a surfactant, based on the weight of the binder solution.
[0043] In one embodiment, the binder solution is prepared by first mixing lignin in ammonia with a carbohydrate reactant and an epoxy-based crosslinker, followed by the addition of the polyamine.
[0044] In one embodiment, the binder solution is prepared by adding a carbohydrate reactant and a polyamine to a mixture of lignin in the form of a solution, wherein an epoxy-based crosslinker has been added to the solution prior to the addition of the carbohydrate reactant and the polyamine.
[0045] In one embodiment, the adhesive solution is prepared by first mixing the carbohydrate reactant and the polyamine, and then adding the lignin in the form of a solution and the epoxy-based crosslinker. In one embodiment, before adding the lignin in the form of a solution and the epoxy-based crosslinker, the carbohydrate reactant and the polyamine are mixed for at least one minute, such as for at least 2 minutes or for at least 5 minutes or for at least 10 minutes. Preferably, before adding the lignin in the form of a solution and the epoxy-based crosslinker, the step of mixing the carbohydrate reactant and the polyamine is carried out at a temperature in the range of 10°C to 30°C, such as at room temperature or at a temperature of about 15°C to 25°C. In one embodiment, the adhesive solution is prepared by first mixing the lignin solution with the carbohydrate reactant and the epoxy-based crosslinker until the carbohydrate is dissolved, and then adding the polyamine. In one embodiment, the adhesive solution is prepared by first mixing the lignin solution with the carbohydrate reactant and mixing until the carbohydrate is dissolved, and then adding the epoxy-based crosslinker and the polyamine.
[0046] During the production of a fibrous insulation product, a binder solution as described herein may be applied to the fibrous material (e.g., sprayed onto a mat or onto fibers as it enters a forming area). As the binder solution contacts the mineral fibers, residual heat from the mineral fibers (note that, for example, glass fibers are made of molten glass and thus may contain residual heat) and the flow of air through and / or around the product will cause a portion of the water to evaporate from the binder solution. Removal of the water leaves the remaining components of the binder resin on the fibers as a coating of a viscous or semi-viscous high solids mixture. The coating of the viscous or semi-viscous high solids mixture acts as a binder resin. At this point, the mat is still uncured. In other words, the uncured binder resin acts to bind the fibers in the mat.
[0047] The uncured binder resin described above may be cured. For example, the process of making a cured insulation product may include a subsequent step in which heat is applied to cause a chemical reaction in the uncured binder resin. For example, in the case of making a glass fiber insulation product or other mineral fiber insulation product, after the binder solution has been applied to the fibers and dehydrated, the uncured insulation product may be transferred to a curing oven. The uncured insulation product is heated in the curing oven (e.g., heated to from about 150° C. to about 320° C.) so that the binder resin is cured. The binder resin thus cured is a formaldehyde-free, waterproof binder resin that binds the fibers of the fibrous insulation product together. Drying and heat curing may occur either sequentially, simultaneously, contemporaneously, or concurrently.
[0048] The uncured fiber product typically comprises from about 3% to about 40% by weight dry binder solids (total uncured solids). In one embodiment, the uncured fiber product comprises from about 5% to about 25% dry binder solids. In one embodiment, the uncured fiber product comprises from about 50% to about 97% by weight fibers.
[0049] Cured adhesive resin is the product that makes adhesive resin solidify.Term curing indicates that adhesive resin has been exposed to the condition that causes chemical change.The example of these chemical changes may include but is not limited to, (i) covalent bonding, (ii) hydrogen bonding of adhesive component, and (iii) polymer and / or oligomer chemical crosslinking in adhesive resin.Compared with uncured adhesive resin, these changes can improve the durability and solvent resistance of adhesive resin.Curing adhesive resin can obtain the formation of thermosetting material.In addition, compared with uncured adhesive resin, curing adhesive resin can obtain the improvement of adhesion between materials in the set.Curing can be caused by one or more conditions of for example heat, microwave radiation and / or causing the chemical change mentioned above.
[0050] In cases where chemical changes in the binding resin result in the release of water, such as polymerization and cross-linking, curing can be determined by the amount of water released being above that which would occur from drying alone. Techniques for measuring the amount of water released during drying compared to when curing the binding resin are well known in the art.
[0051] Example
[0052] Example 1 - Preparation of lignin-ammonia solution
[0053] The lignin ammonia solution was prepared by first adding 211 g of powdered lignin (95% solids when measured using a laboratory infrared moisture analyzer) and 685 g of water to a 1 L glass reactor at room temperature and stirring until the lignin was completely and evenly dispersed. Subsequently, 104 g of a 28-30% ammonia solution was added to the lignin dispersion. The composition was stirred for 60 minutes to ensure complete dissolution of the lignin.
[0054] Example 2 - Preparation of lignin-ammonia solution with plasticizer.
[0055] The lignin-ammonia solution with plasticizer is prepared by adding 211g of powdered lignin (95% solid content when measured using a laboratory infrared moisture analyzer), 685g of water and 50g of PEG400 to a 1L glass reactor at room temperature, and stirring until the lignin is completely and evenly dispersed. Subsequently, 104g of 28-30% ammonia solution is added to the lignin dispersion. The composition is stirred for 60 minutes to ensure complete dissolution of the lignin.
[0056] Example 3 - Preparation of glass rod samples for mechanical testing
[0057] If necessary, the binder solution was diluted with water and combined with a 1% solution of 3-aminopropyltrimethoxysilane (APTES) in water to obtain a final solution with a total concentration of 20-23% (total DS) and a concentration of 0.5% APTES.
[0058] The adhesive was mixed with spherical glass beads (Sibelco 300-400 μm in average size) (a model system traditionally employed in the art of simulating the interaction of resins with glass fibers) and stirred thoroughly using a spatula to obtain a paste of uniform thickness with a binder-on-glass concentration of 4%.
[0059] The paste was transferred to a silicone mold consisting of 8 identical rectangular cavities with a length of 215 mm, a width of 107 mm, and a thickness of 16 mm.
[0060] The paste was evenly distributed among all 8 cavities and the silicone mold was transferred to an oven and subjected to heating at 200°C for 60 min.
[0061] After heating, the mold was allowed to cool to room temperature and 8 identical solid sticks were separated from the mold and stored for further analysis.
[0062] Example 4 - Mechanical Properties of Glass Rod Samples
[0063] The mechanical properties of the glass rods were measured in terms of dry strength (strength of a dry glass rod) and wet strength (strength of a glass rod after conditioning at 80° C. in water for 2 h).
[0064] For dry strength and wet strength, the glass rods were divided into two groups. The samples for dry strength were analyzed as they were. The samples for wet strength were analyzed immediately after conditioning at 80° C. in water for 2 h.
[0065] The weight of the sample before and after conditioning is obtained to measure the water absorption of the sample.
[0066] Strength is measured as follows: Use a caliper to obtain the dimensions of the glass rod. Mount the glass rod on a 65 mm support fixture consisting of two anvils, equally spaced from the center point. Slowly lower the upper anvil to the center point at a constant rate. Record the force at the breaking point of the specimen and convert it to strength at break using the dimensions of the rod.
[0067] Example 5
[0068] By 41g of the lignin solution from Example 2, 4.9g of Jeffamine T403 (polyetheramine), 3.3g of monohydrated glucose, 2.1g of polyethylene glycol diglycidyl ether, 13g of water and 4g of 1% of 3-aminopropyl trimethoxysilane are weighed into a 250ml plastic container, and a wooden stick is used to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads are weighed into a beaker and the lignin mixture is poured on the top of sand (sand) and mixed for 2 minutes. Subsequently, glass rods are prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods are hard and stable after curing in an oven. The dimensions of the rods used for each test are height x thickness x length: 26mm x 18mm x 103mm.
[0069] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0070] The glass rods were evaluated using a 3-point bend test. The flexural strengths before and after water immersion are provided in Table 1.
[0071]
[0072] Table 1. Flexural strength of sand bars with and without conditioning
[0073] Example 6
[0074] By weighing the lignin solution of 51.5g from Example 2, 3.1g of Jeffamine T403, 2.1g of glucose, 2.6g of polyethylene glycol diglycidyl ether, 7g of water and 4g of 1% 3-aminopropyl trimethoxysilane into a 250ml plastic container, and using a wooden stick to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in an oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x18mm x 103mm.
[0075] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0076] The glass rods were evaluated using a 3-point bend test. The flexural strengths before and after water immersion are provided in Table 2.
[0077]
[0078] Table 2. Flexural strength of sand bars with and without conditioning
[0079] Example 7
[0080] By weighing 48.5g of lignin solution from Example 2, 2.9g of Jeffamine T403, 1.9g of glucose, 1g of polyethylene glycol diglycidyl ether, 10g of water and 4g of 1% 3-aminopropyl trimethoxysilane into a 250ml plastic container, and using a wooden stick to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in an oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x18mm x 103mm.
[0081] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0082] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 3.
[0083]
[0084] Table 3. Flexural strength of sand bars with and without conditioning
[0085] Example 8
[0086] By weighing the lignin solution of 51.3g from Example 2, 1.6g of Jeffamine T403, 1g of glucose, 2.6g of polyethylene glycol diglycidyl ether, 10g of water and 4g of 1% 3-aminopropyl trimethoxysilane into a 250ml plastic container, and using a wooden stick to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake at 200°C in an oven for 1 hour. All glass rods were hard and stable after curing in an oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x18mm x 103mm.
[0087] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0088] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 4.
[0089]
[0090] Table 4. Flexural Strength of Sandy Bars with and without Conditioning
[0091] Example 9
[0092] By weighing the lignin solution of 56g from Example 1, 3.4g of Jeffamine T403, 2.2g of glucose, 1.1g of polyethylene glycol diglycidyl ether, 15g of water and 4g of 1% 3-aminopropyl trimethoxysilane into a 250ml plastic container, and using a wooden stick to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake at 200°C in an oven for 1 hour. All glass rods were hard and stable after curing in an oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x18mm x 103mm.
[0093] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0094] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 5.
[0095]
[0096] Table 5. Flexural strength of sand bars with and without conditioning
[0097] Example 10
[0098] Solution is prepared by weighing and stirring 2.3g glucose, 4.5g hexamethylenediamine (HMDA) and 4.5g water. The solution is added to the adhesive composition of 1% 3-aminopropyltrimethoxysilane of the lignin solution of 45g from embodiment 2 in a 250ml plastic container, 2.3g of polyethylene glycol diglycidyl ether and 4g, and a wooden stick is used to stir for 2 minutes. Subsequently, 450g glass beads are weighed in a beaker and the lignin mixture is poured on the top of sand and mixed for 2 minutes. Subsequently, glass rods are prepared by putting glass-adhesive mixture into a silicone mold to bake at 200 ℃ in an oven for 1 hour. All glass rods are hard and stable after curing in an oven. The size of the rod for each test is height x thickness x length: 26mm x 18mm x 103mm.
[0099] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0100] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 6.
[0101]
[0102] Table 6. Flexural Strength of Sandy Bars with and without Conditioning
[0103] Embodiment 11
[0104] The solution was prepared by weighing and stirring 1.8g maltose, 2.7g Jeffamine T403 and 9g water. The solution was added to the lignin solution of 45g from Example 2, 2.3g of polyethylene glycol diglycidyl ether and 4g of 1% of the adhesive composition of 3-aminopropyltrimethoxysilane in a 250ml plastic container, and stirred with a wooden stick for 2 minutes. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in the oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x 18mm x 103mm.
[0105] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0106] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 7.
[0107]
[0108] Table 7. Flexural strength of sand bars with and without conditioning
[0109] Example 12
[0110] By weighing the lignin solution of 51.5g from Example 2, 3.1g of Jeffamine T403, 2.1g of glucose, 4g of water and 4g of 1% 3-aminopropyl trimethoxysilane in a 250ml plastic container, and using a wooden stick to stir for 2 minutes to prepare an adhesive composition. Subsequently, 450g of glass beads were weighed in a beaker and the lignin mixture was poured on the top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in an oven. The dimensions of the rods tested each time were height x thickness x length: 26mm x 18mm x103mm.
[0111] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0112] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 8.
[0113]
[0114] Table 8. Flexural strength of sand bars with and without conditioning
[0115] Embodiment 13
[0116] Prepare solution by weighing and stirring 20g glucose, 20g hexamethylenediamine (HMDA), 60g water.By weighing 39.2g lignin HMDA solution, 5.2g glucose, 15g water and 4g 1% 3-aminopropyl trimethoxysilane in 250ml plastic container and stirring with wooden stick to prepare adhesive composition for 2 minutes.Subsequently, 450g glass beads are weighed in beaker and lignin mixture is poured on the top of sand and mixed to continue 2 minutes.Subsequently, by glass-adhesive mixture is put into silicone mold to prepare glass rod at 200 ℃ of baking in baking oven for 1 hour.All glass rods are hard and stable after curing in baking oven.The size of the rod for each test is height x thickness x length: 26mm x18mm x 103mm.
[0117] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0118] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 9.
[0119]
[0120] Table 9. Flexural strength of sand bars with and without conditioning
[0121] Example 14 (Comparative Example)
[0122] The solution was prepared by weighing and stirring 12g glucose, 18g Jeffamine T403, 52.89g water and 17.2g of 29% ammonia solution. Subsequently, 60g of the solution and 4g of 1% 3-aminopropyltrimethoxysilane were added to a 250ml plastic container and stirred with a wooden stick for 2 minutes. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in the oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x 18mm x 103mm.
[0123] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0124] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 10.
[0125]
[0126] Table 10. Flexural strength of sand bars with and without conditioning
[0127] Example 15 (Comparative Example)
[0128] The solution was prepared by weighing and stirring 12g glucose, 18g Jeffamine T403, 52.89g water and 17.2g of 29% ammonia solution. Subsequently, 51.4g of the solution, 2.6g of polyethylene glycol diglycidyl ether, 6g of water and 4g of 1% of 3-aminopropyl trimethoxysilane were added to a 250ml plastic container and stirred with a wooden stick for 2 minutes. Subsequently, 450g of glass beads were weighed into a beaker and the lignin mixture was poured on top of the sand and mixed for 2 minutes. Subsequently, glass rods were prepared by placing the glass-adhesive mixture into a silicone mold to bake in an oven at 200°C for 1 hour. All glass rods were hard and stable after curing in the oven. The dimensions of the rods used for each test were height x thickness x length: 26mm x 18mm x 103mm.
[0129] The glass rods were post-cured for 24 hours and immersed in a water bath at 80° C. for 2 hours.
[0130] The glass rods were evaluated using a 3-point bend test. The flexural strength before and after water immersion is provided in Table 11.
[0131]
[0132] Table 11. Flexural strength of sand bars with and without conditioning
[0133] In view of the above specific embodiments of the present invention, other modifications and variations will become apparent to those skilled in the art. However, it should be apparent that such other modifications and variations can be implemented without departing from the spirit and scope of the present invention.
Claims
1. A binding resin comprising the reaction product of a carbohydrate reactant, lignin, an epoxy-based crosslinker, and a polyamine, wherein the carbohydrate reactant is selected from a monosaccharide, a disaccharide, or an oligosaccharide, and wherein the polyamine is a primary polyamine selected from a diamine, a triamine, a tetraamine, and a pentamine, and wherein the polyamine is H2N-Q-NH2, wherein Q is C1-C 10 Alkyl, cycloalkyl, C1-C 10 heteroalkyl or cycloheteroalkyl, each of which is optionally substituted; and wherein the lignin is provided as a solution, and wherein the weight ratio of carbohydrate to polyamine is in the range of from 1:100 to 100:1, and wherein the weight ratio of lignin to carbohydrate is between 1:100 and 100:1, calculated on a dry lignin to dry carbohydrate basis, and wherein the amount of lignin in the binding resin is in the range of from 1 wt % to 50 wt %, calculated on a dry lignin and dry binding resin basis.
2. The binding resin according to claim 1, wherein the carbohydrate reactant is a disaccharide.
3. The binding resin according to claim 2, wherein the disaccharide is selected from sucrose, lactose and maltose.
4. The adhesive resin according to any one of claims 1 to 3, wherein the polyamine is selected from hexamethylenediamine, polyetheramine, 1,6-diaminohexane, 1,5-diamino-2-methylpentane, 3-(aminomethyl)-3,5,5-trimethylcyclohexane-1-amine, diethylenetriamine, 1-piperazineethylamine, bis(hexamethylene)triamine, triethylenetetramine and tetraethylenepentamine.
5. The binding resin according to any one of claims 1 to 4, wherein the lignin is not chemically modified after it is extracted and separated from the wood.
6. The binding resin according to any one of claims 1 to 5, wherein the lignin solution is a solution of lignin in ammonia and / or an organic base.
7. The binding resin according to any one of claims 1 to 6, wherein the weight ratio of lignin to carbohydrate is in the range from 1:1 to 5:1, calculated on a dry solids basis.
8. The binder resin according to any one of claims 1 to 7, wherein the weight ratio of lignin to polyamine is from 2:1 to 5:1, calculated on a dry solids basis.
9. The binding resin according to any one of claims 1 to 8, wherein the weight ratio of epoxy-based crosslinking agent to lignin is in the range from 1:100 to 10:1, preferably from 2:100 to 1:1, calculated on a dry solids basis.
10. The adhesive resin according to any one of claims 1 to 8, wherein the epoxy-based crosslinking agent is selected from glycerol diglycidyl ether, polyglycerol polyglycidyl ether, glycerol triglycidyl ether, sorbitol polyglycidyl ether, alkoxylated glycerol polyglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane diglycidyl ether, polyoxypropylene glycol diglycidyl ether, polyoxypropylene glycol triglycidyl ether, diglycidyl ether of cyclohexanedimethanol, resorcinol diglycidyl ether, isosorbide diglycidyl ether, pentaerythritol tetraglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether having 2 to 9 ethylene glycol units, propylene glycol diglycidyl ether having 1 to 5 propylene glycol units Glycidyl ethers, diglycidyl-, triglycidyl- or polyglycidyl-ethers of carbohydrates, diglycidyl-, triglycidyl- or polyglycidyl-esters of carbohydrates, diglycidyl-ethers or diglycidyl esters of salicylic acid, vanillic acid or 4-hydroxybenzoic acid, epoxidized or glycidyl-substituted plant-based phenolic compounds or epoxidized plant-based oils, tris(4-hydroxyphenyl)methane triglycidyl ether, N,N-bis(2,3-epoxypropyl)aniline, p-(2,3-epoxypropyloxy-N,N-bis(2,3-epoxypropyl)aniline, diglycidyl ethers of bis-hydroxymethylfuran, and / or diglycidyl ethers of terminal diols having a linear carbon chain of 3 to 6 carbon atoms.
11. A fibrous insulation product comprising the binding resin according to any one of claims 1 to 9 and a fibrous material.
12. A fibrous insulation product according to claim 11, wherein the fibrous material is selected from the group consisting of glass fibers, mineral fibers, aramid fibers, ceramic fibers, metal fibers, carbon fibers, polyimide fibers, polyester fibers and rayon fibers and cellulose fibers.
13. The fibrous insulation product of claim 11, wherein the fibrous material is selected from glass fibers or mineral fibers.
14. A process for preparing a binding resin according to any one of claims 1 to 9, wherein a carbohydrate reactant selected from a monosaccharide, a disaccharide or an oligosaccharide is mixed with a primary polyamine selected from a diamine, a triamine, a tetraamine and a pentamine, and wherein the polyamine is H2N-Q-NH2, wherein Q is C1-C 10 Alkyl, cycloalkyl, C1-C 10 heteroalkyl or cycloheteroalkyl, each of which is optionally substituted, wherein mixing is performed at a temperature in the range of from 10°C to 30°C for at least one minute, followed by the addition of lignin and the epoxy-based crosslinker as a solution.
Citation Information
Patent Citations
Binder compositions and associated methods
US20050202224A1
Binders and materials made therewith
US20070027283A1
Method for separating lignin from black liquor
WO2006031175A1
binders
WO2009019235A1